Akidah dan Etika: Relasi antara Keyakinan dengan Nilai Moral - Andini, Melly (UIN Sumatera Utara, 2023)
In the context of global society and the social changes that occur in the current era of globalization, ethical challenges such as discrimination, promiscuity, hedonism and other forms of moral crisis arise. One of the factors that causes this behavior is a lack of understanding of the individual's creed or religious beliefs. The presence of Islamic beliefs and moral values in the midst of modern life is considered capable of alleviating various forms of moral crises that occur. Therefore, attention to faith, ethics and moral issues becomes increasingly important to study. This article aims to reveal the relationship between faith, ethics and moral values in Islamic teachings. The method used is literature study or literature review by collecting and observing theories, data and information from various trusted written sources. The results of this research reveal that there is a significant relationship between religious beliefs and Islamic moral values. These relationships will mutually influence each other and will have implications for individual behavior in life.Keywords: Creed, Ethics, Religious Beliefs, Moral Values, and Islam.